2017
DOI: 10.7759/cureus.1322
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks and the Risk of Cardiovascular Disease: A Review of Current Literature

Abstract: Energy drinks (EDs) are commonly used as a dietary supplement by young adolescents and adults. They are often used as a source of energy in order to enhance physical and mental performance. EDs contain a variety of substances, but caffeine is the main component. Safety has been the biggest concern associated with consuming EDs. Case reports, observational studies, and meta-analyses have been done in order to determine the effects of EDs on cardiovascular changes. The detrimental effects of EDs are cardiac arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 42 publications
1
33
0
2
Order By: Relevance
“…There are case reports of ventricular arrhythmias and sudden cardiac death secondary to EDs. These were reported in both patients with and without structural heart disease [5]. Ehlers et al demonstrated that heavy caffeine consumption may increase the risk of adverse effects including, nervousness, anxiety, insomnia, heart palpitations, and tachycardia [12].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are case reports of ventricular arrhythmias and sudden cardiac death secondary to EDs. These were reported in both patients with and without structural heart disease [5]. Ehlers et al demonstrated that heavy caffeine consumption may increase the risk of adverse effects including, nervousness, anxiety, insomnia, heart palpitations, and tachycardia [12].…”
Section: Discussionmentioning
confidence: 98%
“…Safety has been the biggest concern associated with consuming EDs. Over the past decade, it has been noticed that unexplained cardiovascular events (including death, cardiac arrest, atrial and ventricular arrhythmia, and myocardial infarction) in some young individuals developed after consuming EDs [1][2][3][4][5]. It is known that several stimulants are included in formulas of different EDs and the key ingredient in EDs is a high dose of caffeine, which is a methylxanthine, part of a chemical family that includes theophylline and aminophylline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also stated that certain people may be more sensitive and genetically more susceptible to arrhythmias than others. Coronary vasospasm (3), ST elevation myocardial infarction (5), aortic aneurysm dissection (6), cardiac arrest (4), cardiomyopathy, prolonged QT interval incidents are reported in connection with consumption of ED (7). The probable mechanism involved in the development of myocardial infarction after ED consumption is endothelial dysfunction and platelet aggression caused by arachidonic acid (7,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary vasospasm (3), ST elevation myocardial infarction (5), aortic aneurysm dissection (6), cardiac arrest (4), cardiomyopathy, prolonged QT interval incidents are reported in connection with consumption of ED (7). The probable mechanism involved in the development of myocardial infarction after ED consumption is endothelial dysfunction and platelet aggression caused by arachidonic acid (7,8,9). Especially after consumption of two or more boxes of ED, a male patient aged seventeen suffered from coronary artery spasm and another patient suffered from cardiac arrest (3).…”
Section: Discussionmentioning
confidence: 99%